“Leave No One Behind" Slogan On Street Children Empowerment By The Save Street Children Sidoarjo Community - Fitriani, Andine; Rifqi Nabila, Maia; Mustajab, Hidayatul; Rudy Hartanto, Dhimas (DIDAKTIKA, 2025)
This study aims to analyze the role of Save Street Children Sidoarjo (SSCS) in accelerating the Leave No One Behind Slogan through the street child empowerment program in Sidoarjo. Different from previous research, this study integrates the Leave No One Behind slogan within the framework of human development as a key conceptual approach. The research uses qualitative methods with a case study approach, as well as data collection techniques through in-depth interviews and direct observation. The results of the study show that SSCS actually implements the Leave No One Behind slogan by providing access to education and skills training for street children. These programs not only focus on meeting basic needs, but also encourage individual capacity building within the framework of human development. These findings confirm that the role of SSCS is aligned with the commitment to inclusive and sustainable development.